Structural determinants of oxygen resistance and Zn 2+ -mediated stability of the [FeFe]-hydrogenase from Clostridium beijerinckii - Jifu Duan; Andreas Rutz; Akihiro Kawamoto; Shuvankar Naskar; Kristina Edenharter; Silke Leimkühler; Eckhard Hofmann; Thomas Happe; Genji Kurisu (Proceedings of the National Academy of Sciences, 2025)
[FeFe]-hydrogenases catalyze the reversible two-electron reduction of two protons to molecular hydrogen. Although these enzymes are among the most efficient H 2 -converting biocatalysts in nature, their catalytic cofactor (termed H-cluster) is irreversibly destroyed upon contact with dioxygen. The [FeFe]-hydrogenase CbA5H from Clostridium beijerinckii has a unique mechanism to protect the H-cluster from oxygen-induced degradation. The protective strategy of CbA5H was proposed based on a partial protein structure of CbA5H’s oxygen-shielded form. Here, we present a cryo-EM structure of 2.2 Å resolution from the entire enzyme in its dimeric and active state and elucidate the structural parameters of the reversible cofactor protection mechanism. We found that both subunits of the homodimeric structure of CbA5H have a Zn 2+ -binding four-helix domain, which does not play a role in electron transport as described for other complex protein structures. Biochemical data instead confirm that two [4Fe-4S] clusters are responsible for electron transfer in CbA5H, while the identified zinc atom is critical for oligomerization and protein stability.